2004
DOI: 10.1111/j.1601-1848.2004.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced aggression in AMPA‐type glutamate receptor GluR‐A subunit‐deficient mice

Abstract: The importance of AMPA‐type glutamate receptors has been demonstrated in neuronal plasticity and in adaptation to drugs of abuse. We studied the involvement of AMPA receptors in social interaction and anxiety and found that in several paradigms of agonistic behavior naïve male mice deficient for the GluR‐A subunit‐ containing AMPA receptors are less aggressive than wild‐type littermates. GluR‐A deficient mice and wild‐type littermates exhibited similar basic behavior and reflexes as monitored by observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 60 publications
(137 reference statements)
4
62
0
2
Order By: Relevance
“…An earlier study found that KO fail to show the normal increase in conspecific aggression that occurs in mice following social isolation. 34 Taken together, these data suggest that these mice do not respond normally to social signals and/or fail to appropriately organize behavior in social contexts.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…An earlier study found that KO fail to show the normal increase in conspecific aggression that occurs in mice following social isolation. 34 Taken together, these data suggest that these mice do not respond normally to social signals and/or fail to appropriately organize behavior in social contexts.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, earlier work has shown that tissue levels of DA and its metabolites are not grossly aberrant in KO. 34 Thus, loss of DA clearance appears to result from an alteration in DA clearance capacity, possibly resulting from changes in DAT functionality and/or trafficking, rather than an alteration in DA release, DAT availability or a more general change in the DA synthesis or availability. Loss of DA clearance in KO and the predicted corollary increase in the magnitude and duration of extracellular levels of DA in striatum provides one plausible mechanism driving the abnormal GluR1 KO behavioral responses to conditions in which the DA system is activated, such as novelty, stress and high cognitive demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is not surprising that complex and conflicting results for anxiety-related behavior have also been reported in global Gria1-knockouts (Barkus et al, 2012). Increased anxiety-like behavior has been shown in the hyponeophagia test (Bannerman et al, 2004), while reduced anxiety-like behavior was found in the elevated plus maze and Dark-Light Box (Fitzgerald et al, 2010;Vekovischeva et al, 2004). This apparent inconsistency could be a result of the impaired short-term habituation and novelty induced hyperlocomotion in global Gria1-knockouts that complicate analysis of anxiety behavior (Barkus et al, 2012;Chourbaji et al, 2008c;Wiedholz et al, 2008).…”
Section: Behavioral Phenotypementioning
confidence: 99%
“…Thus, as demonstrated in hippocampal CA1 pyramidal cells, GLUA1-containing AMPA receptors are not critically involved in synaptic signal transmission, but they constitute a pool of extrasynaptic AMPA receptors that is necessary for activityinduced increases in synaptic transmission (Jensen et al, 2003;Zamanillo et al, 1999). Global GLUA1-deficient mice exhibit impairments in many different forms of learning and memory (for review see (Sanderson et al, 2008) as well as alterations in depressive and anxiety-like behaviors (Bannerman et al, 2004;Chourbaji et al, 2008c;Fitzgerald et al, 2010;Vekovischeva et al, 2004). Given the involvement of 5-HT in mood and anxiety, we hypothesised that these latter effects of the global Gria1 deletion involve changes in 5-HT function.…”
Section: Introductionmentioning
confidence: 99%